Coexisting Primary Sclerosing Cholangitis and Autoimmune Hepatitis: Overlapping Challenges in Diagnosis and Treatment - Hannah W. Fiske; Firrah Saeed; Christopher Ward; Boris Sinayuk; Veronica Ulici; Michael Curry; Edward Feller; Samir A. Shah (Case Reports in Gastroenterology, 2024)
Introduction: Hepatobiliary overlap syndromes describe the coinciding presentation of more than one immune-mediated biliary and liver disease in a single patient and present complex challenges in diagnosis and treatment. We report a case of ulcerative colitis with primary sclerosing cholangitis and autoimmune hepatitis overlap syndrome responsive to vancomycin. Case Presentation: The patient is a 30-year-old female with known ulcerative pancolitis and autoimmune hepatitis. She presented to the emergency department with a constellation of gastrointestinal symptoms, including diffuse lower abdominal pain, bloody diarrhea, and nausea with bilious vomiting. Subsequent imaging revealed the additional diagnosis of primary sclerosing cholangitis, and she was diagnosed with overlap syndrome. Multiple treatment regimens were trialed with minimal improvement. She eventually achieved normalization of both clinical status and biochemical markers after the addition of vancomycin. Conclusion: Vancomycin is an underutilized therapy; its potential role in primary sclerosing cholangitis and autoimmune hepatitis overlap syndrome has not been previously reported.